Comparative Analysis of Petaurus Cryptic Species of ‘Sugar Glider’ from Australia and New Guinea Using 3D Geometric Morphometrics - Meagan Powley; Katarina Mikac (Animals)
The description of the Petaurus sp. has been ongoing since first described and especially within the last fifteen years. Recently from the known P. breviceps species, three subspecies have been recognized at the species level. Two of these species, P. notatus and P. ariel, have been geographically described throughout Australia; however, the northeast Queensland labeled P. breviceps remain unrevised. A third species, P. papuanus, is located throughout New Guinea and is associated with at least one divergence event to Australia. Our research used geometric morphometrics and linear measurements to compare known Australian species with specimens from Cape York and New Guinea. No significant shape difference was found between the known specimens of P. notatus and Cape York specimens. Our findings support an earlier identification of P. notatus (P. longicaudatus) at this location. Significant shape variation was found between Cape York specimens and New Guinea, indicating no association with the New Guinea species. Significant shape changes were also found in island specimens when compared with the mainland New Guinea specimens, which was likely a result of their isolation and accelerated evolutionary responses to novel environments. No significant shape change was found for mainland New Guinea specimens, which was likely associated with overlapping distribution and hybridization.